PP585 A New Hope For Breast Cancer Survivors: Early Assessment Of A Breast Cancer Vaccine. (December 2020) - Jamaluddin, Norrina; Ghazali, Izzuna Mudla Mohamed; Sabirin, Junainah
Abstract : Introduction: Breast cancer is the most frequent cancer among women globally, impacting 2.1 million women each year, causing the greatest number of cancer-related deaths among women. In Malaysia, the new cases of breast cancer comprised of 32.7 percent of all new cancer cases in women as reported by The International Agency for Research on Cancer (IARC). The recurrence rate was about 16.4 percent post-mastectomy. This early assessment is to evaluate the effectiveness and safety of a breast cancer vaccine. Methods: A systematic review was conducted. Searches were done through PubMed, Medline and ClinicalTrial.gov. The articles were selected based on inclusion and exclusion criteria and appraised using Critical Appraisal Skills Programme (CASP) checklist. More than twenty cancer vaccines under development were identified. Results: The most advanced breast cancer vaccine is Nelipepimut-S (NPS). In a Phase 2b clinical trial, improvement disease-free survival (DFS) in the NPS group was 89.8 percent. The DFS rate in the NPS group was 92.6 percent for triple negative patients. Median DFS in the NPS group [hazard ratio (HR): 0.26 (95% confidence interval, Cl: 0.08–0.81)] showed a significant difference. A projection study showed the cost-effectiveness will be 90 percent success if the cost less than USD1, 000 per patient. No safety issues were reported. Conclusions: Early assessment showed potential benefit in patient with triple-negative breast cancer (TNBC). However, further research is required to ensure its efficacy, safety, and cost-effectiveness.